Counselling for physical activity, life-space mobility and falls prevention in old age (COSMOS): protocol of a randomised controlled trial. Issue 9 (24th September 2019) - Edgren, Johanna; Karinkanta, Saija; Rantanen, Taina; Daly, Robin; Kujala, Urho M; Törmäkangas, Timo; Sievänen, Harri; Kannus, Pekka; Heinonen, Ari; Sipilä, Sarianna; Kannas, Lasse; Rantalainen, Timo; et al.
Abstract : Introduction: The most promising way to promote active life years in old age is to promote regular participation in physical activity (PA). Maintaining lower extremity muscle function with good balance has been associated with fewer falls and the need of help from others. This article describes the design and intervention of a randomised controlled trial (RCT) investigating the effectiveness of a health and PA counselling programme on life-space mobility and falls rates in community-dwelling older adults at the Health Kiosk and/or Service Centre. Methods and analysis: Community-dwelling men and women (n=450) aged 65 years and over with early phase mobility limitation will be recruited to a 24-month RCT with a 24-month follow-up. Participants will be randomly allocated into either a health and PA counselling group (intervention) or relaxation group (control intervention). All participants will receive five group specific face-to-face counselling sessions and 11 phone calls. The counselling intervention will include individualised health counselling, strength and balance training, and guidance to regular PA. The control group will receive relaxation exercises. Outcomes will be assessed at baseline, 12, 24 and 48 months. Primary outcomes are average life-space mobility score and falls rates. Life-space mobility will be assessed by a validated questionnaire. Falls rates will be recorded from fall diaries. Secondary outcomes are data on fall-induced injuries and living arrangements, number of fallers, fracture risk, mean level of PA, physical performance, quality of life, mood, cognition, balance confidence and fear of falling. Data will be analysed using the intention-to-treat principle. Cost-effectiveness of the programme will be analysed. Ancillary analyses are planned in participants with greater adherence. Ethics and dissemination: Ethical approval was obtained from the Ethics Committee of the Tampere University Hospital (R15160). Outcomes will be disseminated through publication in peer-reviewed journals and presentations at international conferences. Trial registration: ISRCTN65406039 ; Pre-results.